3D Modelling and restoration of the Vargfors Basin, Central Skellefte District, Northern Sweden, using gOcad and MOVE software - Vilain, David (2010)
3D modelling is an important step toward better understanding of the current and past geology in the Central Skellefte District. The study of the geometry of the sedimentary Vargfors basin and its contact with the underlying Skellefte Group rocks may lead to further understanding of the geological events that affected the whole Skellefte district, and to new strategy for ore deposit exploration. A 3D geometric model of well understood fault-bound compartments of the Vargfors basin has been built in the geo-modelling software gOcad using geological map, structural measurements and geophysical data as a starting point. The plugin Sparse has proved to be an efficient and intuitive tool to model surfaces where there are few or heterogeneously distributed data. The 3D model gives an intuitive view of the interpreted geology at depth. Moreover, a plausible scenario of structural evolution is proposed using 2D forward and backward modelling using the restoration software MOVE. However, the lack of stratigraphical markers and correlation between the footwall and the hangingwall does not allow a quantitative restoration whereby important geometric parameters of the basin can not be constrained by this method. Validerat; 20101217 (root)